A Defesa Interamericana Diante Dos Cenários De Agressão Ao Continente - Nascimento, Mario Brasil do (Hemisferio - Revista del Colegio Interamericano de Defensa, 2022)
The idea of a collective defense for the American continent emerged as a result of German threats and offensive actions during World War II. With the end of the war, the Cold War between the United States and the former Union of Soviet Socialist Republics, the emergence of nuclear weapons; and the expansion of communism brought new threats to America, requiring the adaptation of the inter-American defense. The adoption of multidimensional security in America has cooled concerns about continental defense.With the rise of China as an economic and military power, the return of a new Cold War between the US and Russia and the emergence of new high- capacity military devices bring to the fore the need for a re-discussion of inter-American relations defense. To maintain peace in America, what inter-American defense system is needed for the future? That is the question